USING STORY TELLING TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT CLASS VIII OF SMP NEGERI 3 LASALIMU - Waode Hanafiah; Baharudin Adu; Farid Farid (English Education Journal, 2020)
The purpose of this study was to determine the increase in vocabulary mastery of the eight grade students of SMP Negeri 3 Lasalimu through local stories. This study used a pre-experimental design. The sample in this study were students of class VIII, amounting to 14 students. The instrument used in this study was a test. The results obtained are: 1) the pretest results obtained an average value of 43.21 and the posttest obtained an average value of 66.07%; 2) based on the results of hypothesis testing, sig. (2-tailed) is 0.000 <0.05, so it can be concluded that Ho was rejected and H1 was accepted. Therefore the use of regional folklore has a positive influence on vocabulary mastery of students in class VIII SMP Negeri 3 Lasalimu in the 2018/2019 academic year.